Introduction: From Concord to Peace. Issue 159 (1st July 2019) - Benjamin, Andrew; Borghesi, Francesco
Abstract : This special issue arose from a workshop on "Peace and Concord from Plato to Lessing", organised by the editors and which took place at the University of Sydney on 18 and 19 September 2017. Central to the work of both the editors is the relationship between the concepts of 'concord', 'peace' and 'dignity' within a setting created by a concern with the development of a philological anthropology. Their work combines both intellectual history and philosophy, a combination that is reflected in the contents of the special issue of Theoria. The importance of these terms is that they allow for another interpretation of the ethical and the political. Central to both is the location of human being within a larger cultural context. That context demands an approach in which philosophy does not exclude history, and history recognises that it is already informed philosophically. If there is a unifying term, it is 'culture'. The approach taken within the larger project starts with the centrality of culture as that which demands to be thought. And yet culture is neither tranquil nor unified. As Walter Benjamin argued, there 'is no document of culture which is not at the same time a document of barbarism'. Allowing for culture's centrality entails a reconfiguration of both philosophy and intellectual history.